Cold storage effects on flesh quality of rainbow trout Oncorhynchus mykiss (Walbaum, 1792) fed diets containing different vegetable oils. (2nd April 2016) - Yildiz, M.; Kose, I.; Issa, G.; Kahraman, T.; Guven, E.; Baltaci, M. A.; Yuruten, K.
Summary: The intention of this experiment was to assess the effects of different sources of dietary lipid on the fatty acid composition of the fillet and liver and the flesh quality traits of rainbow trout ( Oncorhynchus mykiss ) after a 70‐day feeding period. Four iso‐nitrogenous (approx. 51% crude protein) and iso‐lipidic (approx. 14% crude lipid) experimental diets were formulated. The control diet contained only fish oil (FO) as the primary lipid source. In the other three dietary treatments, fish oil was replaced by 100% (LO30/SO35/SFO35) and 70% (FO30/LO35/SO35 or FO30/SO35/SFO35) sesame oil (SO), linseed oil (LO), or sunflower oil (SFO). Triplicate groups of 40 rainbow trout (~46 g) held under similar culture conditions were hand‐fed daily to apparent satiation for 70 days. At the end of the feeding trials, no difference in growth performance among experimental groups was noted (P > 0.05). There were some differences in the proximate composition of fish fillets (P < 0.05): the eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) levels were highest in fish fed the control diet (P < 0.05); and EPA and DHA levels in fish fed the FO30/LO35/SO35 diet were closest to the control diet (P < 0.05). In contrast, fish fed the diet containing 100% plant oils (LO30/SO35/SFO35) had the highest level of total n‐6 fatty acids in the fillet and liver. In a 12‐day refrigerated storage at 1°C the thiobarbituric acid (TBA), trimethylamin nitrogen (TMA‐N) and pH values gradually increased in all dietary groups (P < 0.05). The chemical indicators of spoilage, TBA, TMA‐N, and pH values were within the limit of acceptability for human consumption.